Serum microRNAs in ASD: Association With Monocyte Cytokine Profiles and Mitochondrial Respiration - Jyonouchi, Harumi; Geng, Lee; Toruner, Gokce A.; Rose, Shannon; Bennuri, Sirish C.; Frye, Richard E. (Frontiers in Psychiatry, 2019)
Our previous research has shown that purified peripheral blood monocytes (PRMo) from individuals who are diagnosed with autism spectrum disorders (ASD) and have innate immune abnormalities reveal altered interleukin-1ß (IL-1ß)/IL-10 ratios. We also found, in separate studies, that microRNA (miRNA) expression in PBMo and mitochondrial respiration in peripheral blood mononuclear cells (PBMCs) differed in the IL-1ß/IL-10 based ASD subgroups. This study explored whether serum miRNAs are associated with both altered innate immune responses and changes in mitochondrial respiration as a link of regulatory mechanisms for these two common abnormalities in ASD subjects. Serum miRNA levels were examined by high throughput deep sequencing in ASD and non-ASD control sera with concurrent measurement of PBMo cytokine production and mitochondrial respiration by PBMCs. ASD samples were examined as a whole group and with respect to the previously defined IL-1ß/IL-10 based ASD subgroups (high, normal, and low groups)(Jyonouchi et al., 2017b). Serum miRNA levels differed between the overall ASD sera (N=116) and non-ASD control sera (N=35) and also differed across the IL-1ß/IL-10 based ASD subgroups. Specifically, miRNA levels were increased and decreased in 8 and 9 miRNAs, respectively, in the high ratio ASD subgroup (N=48). In contrast, the low (N=25) and normal (N=43) ratio ASD subgroups, only showed decreased miRNAs levels (18, and 10 miRNAs, respectively). Gene targets of the altered miRNAs in the high and/or low IL-1β/IL-10 ratio ASD subgroups were associated with pathways critical for monocyte functions and metabolic regulation. Gene targets of the altered miRNAs in all the ASD subgroups were associated with pathways of neuronal development and synaptic plasticity, along with cell proliferation/differentiation. ASD subgroup-specific associations were observed between serum miRNA expression and IL-1ß/IL-10 ratios, mitochondrial respiration, and monocyte cytokine profiles (IL-10, CCL2, and TNF-α). In summary, our results indicate that serum levels of select miRNAs may serve as promising biomarkers for screening and monitoring changes in innate immunity and mitochondrial respiration in ASD.